Serum of myeloproliferative neoplasms stimulates hematopoietic stem and progenitor cells - Lubberich, Richard K. (PLoS One, 2018)
BACKGROUND: Myeloproliferative neoplasms (MPN)—such as polycythemia vera (PV), essential thrombocythemia (ET), and myelofibrosis (MF)—are typically diseases of the elderly caused by acquired somatic mutations. However, it is largely unknown how the malignant clone interferes with normal hematopoiesis. In this study, we analyzed if serum of MPN patients comprises soluble factors that impact on hematopoietic stem and progenitor cells (HPCs). METHODS: CD34(+) HPCs were cultured in medium supplemented with serum samples of PV, ET, or MF patients, or healthy controls. The impact on proliferation, maintenance of immature hematopoietic surface markers, and colony forming unit (CFU) potential was systematically analyzed. In addition, we compared serum of healthy young (<25 years) and elderly donors (>50 years) to determine how normal aging impacts on the hematopoiesis-supportive function of serum. RESULTS: Serum from MF, PV and ET patients significantly increased proliferation as compared to controls. In addition, serum from MF and ET patients attenuated the loss of a primitive immunophenotype during in vitro culture. The CFU counts were significantly higher if HPCs were cultured with serum of MPN patients as compared to controls. Furthermore, serum of healthy young versus old donors did not evoke significant differences in proliferation or immunophenotype of HPCs, whereas the CFU frequency was significantly increased by serum from elderly patients. CONCLUSION: Our results indicate that serum derived from patients with MPN comprises activating feedback signals that stimulate the HPCs–and this stimulatory signal may result in a viscous circle that further accelerates development of the disease.